2016
DOI: 10.1016/j.molp.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Roles of HY5 in Plant Growth and Development

Abstract: ELONGATED HYPOCOTYL5 (HY5), a member of the bZIP transcription factor family, inhibits hypocotyl growth and lateral root development, and promotes pigment accumulation in a light-dependent manner in Arabidopsis. Recent research on its role in different processes such as hormone, nutrient, abiotic stress (abscisic acid, salt, cold), and reactive oxygen species signaling pathways clearly places HY5 at the center of a transcriptional network hub. HY5 regulates the transcription of a large number of genes by direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
461
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 527 publications
(480 citation statements)
references
References 113 publications
(166 reference statements)
12
461
0
7
Order By: Relevance
“…HY5 action is further modulated by a number of other factors (Gangappa and Botto, 2016). In this study,…”
mentioning
confidence: 89%
“…HY5 action is further modulated by a number of other factors (Gangappa and Botto, 2016). In this study,…”
mentioning
confidence: 89%
“…The transcription factor HY5 is a key integrator of photomorphogenesis and is involved in light, hormone, and stress signaling (Cluis et al, 2004;Lee et al, 2007;Gangappa and Botto, 2016). HY5 was recently shown to be transported upon light activation from the shoot to the root (Chen et al, 2016).…”
Section: Mobile (Signaling) Chemicalsmentioning
confidence: 99%
“…photomorphogenesis, and it serves as the center of a transcriptional network hub of hormone and light signaling (Gangappa and Botto, 2016). Besides HY5, COP1 also targets factors like the MYB transcription factor LONG AFTER FAR-RED LIGHT1 (Seo et al, 2003), the basic helix-loop-helix protein LONG HY-POCOTYL IN FAR-RED1 (Duek et al, 2004), and even phytochrome A (phyA) and phyB photoreceptors (Seo et al, 2004;Jang et al, 2010).…”
mentioning
confidence: 99%
“…In Arabidopsis , ELONGATED HYPOCOTYL 5 (HY5) is considered as a key signaling player in photomorphogenesis, and directly activates the expression of the R2R3-MYB TF, production of anthocyanin pigment 1 ( PAP1 ) and anthocyanin biosynthesis genes, chalcone synthase ( CHS ), and chalcone isomerase ( CHI ) by binding to their promoters [14,17]. Several studies have therefore shown that genes controlling HY5 can positively and negatively regulate anthocyanin biosynthesis [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…B-box proteins (BBX), which contain one or two B-box domains at their N-terminal region, function as TFs and have roles in plant growth and development [18]. The BBX proteins are classified into five subfamilies based on their phylogeny and domain compositions in Arabidopsis and rice [20,21].…”
Section: Introductionmentioning
confidence: 99%